FORMATION OF THE SCIENTIFIC WORLDVIEW OF STUDENTS IN THE CONDITIONS OF INNOVATIVE EDUCATION - Hakkulova, Sevara (Science technology&Digital finance, 2023)
This article describes innovative education and the formation and development of students' scientific worldview and its essence. Mainly, some methods that should be used in developing the scientific worldview of students and improving their scientific potential have also been mentioned. The future importance of developing an innovative worldview in the educational process is briefly explained.